Production and partial characterization of two types of phytase from aspergillus niger NCIM 563 under submerged fermentation conditions - Soni, Sarvesh Kumar; Khire, Jayant Malhar (World Journal of Microbiology & Biotechnology, 2007)
Novel extracellular phytase was produced by Aspergillus niger NCIM 563 under submerged fermentation conditions at 30 degrees C in medium containing dextrin and glucose as carbon sources along with sodium nitrate as nitrogen source. Maximum phytase activity (41.47 IU/mL at pH 2.5 and 10.71 IU/mL at pH 4.0) was obtained when dextrin was used as carbon source along with glucose and sodium nitrate as nitrogen source. Nearly 13 times increase in phytase activity was observed when phosphate in the form of KH2PO4 (0.004 g/100 mL) was added in the fermentation medium. Physic-chemical properties of partially purified enzyme indicate the possibility of two distinct forms of phytases, Phy I and Phy II. Optimum pH and temperature for Phy I was 2.5 and 60 degrees C while Phy II was 4.0 and 60 degrees C, respectively. Phy I was stable in the pH range 1.5-3.5 while Phy II was stable in the wider pH range, 2.0-7.0. Molecular weight of Phy I and Phy II on Sephacryl S-200 was approximately 304 kDa and 183 kDa, respectively. Phy I activity was moderately stimulated in the presence of 1 mM Mg2+, Mn2+, Ca2+ and Fe3+ ions and inhibited by Zn2+ and Cd2+ ions while Phy II activity was moderately stimulated by Fe3+ ions and was inhibited by Hg2+, Mn2+ and Zn2+ ions at 1 mM concentration in reaction mixture. The Km for Phy I and II was 3.18 and 0.514 mM while Vmax was 331.16 and 59.47 mu mols/min/mg protein, respectively.
Keywords: Aspergillus niger; Phytase; phytate degradation; Poultry feed supplement; Submerged fermentation